The Impact of Education on Social Mobility in North Bali in the Early XX Century - Arta, Ketut Sedana; Yasa, I Wayan Putra; Pageh, I Made (Paramita: Historical Studies Journal, 2021)
This research was intended to examine the impact of education on social mobility in North Bali during the Dutch colonialism era in the early twentieth century. The method used for this research was heuristics, source criticism, interpretation, and historiography, assisted by social science as an analytical tool. The research findings revealed that the colonial era education system in North Bali consisted of two groups, namely primary and secondary education up to the junior high school level as it is today. Europeesche Lagere School (ELS) in Singaraja was built in 1916, while Hollandsch Inlandsche School (HIS) first opened in 1918 in Singaraja, then in Denpasar, followed by Klungkung and Karangasem.The Netherlands also established a Volks School in villages. The development of education and facilities and infrastructure was quite good at that time as evidenced by the number of existing schools totaling 142. The existence of this educational institution provided opportunities for many groups of aristocrats and ordinary people (jaba) to obtain an education. This condition had an impact on the change in the social structure of the Balinese from feudal to modern, where the jaba experienced vertical social mobility. This in turn resulted in competition among aristocrats and jaba, resulting in various organizations such as Surya Kanta and Bali Adnyana. The Surya Kanta organization, which was founded by the jaba, carried out a social movement by demanding equality in society, eliminating ajawera, adapting custom to the times, eliminating asupundung and alangkahi karanghulu, and returning the caste system to religious principles.Penelitian ini dimaksudkan untuk mengkaji dampak pendidikan terhadap mobilitas sosial di Bali Utara pada masa penjajahan Belanda di awal abad ke-20. Metode yang digunakan dalam penelitian ini adalah heuristik, kritik sumber, interpretasi, dan historiografi dengan bantuan ilmu sosial sebagai alat analisis. Hasil penelitian mengungkapkan bahwa sistem pendidikan zaman kolonial di Bali Utara terdiri dari dua golongan, yaitu pendidikan dasar dan menengah sampai dengan tingkat sekolah menengah pertama seperti sekarang ini. Europeesche Lagere School (ELS) di Singaraja dibangun pada tahun 1916, sedangkan Hollandsch Inlandsche School (HIS) pertama kali dibuka pada tahun 1918 di Singaraja, kemudian di Denpasar, disusul oleh Klungkung dan Karangasem. Belanda juga mendirikan Volks School di desa-desa. Perkembangan pendidikan dan sarana prasarana saat itu cukup baik dibuktikan dengan jumlah sekolah yang ada berjumlah 142. Keberadaan lembaga pendidikan ini memberikan peluang bagi banyak golongan bangsawan dan masyarakat biasa (jaba) untuk mengenyam pendidikan. Kondisi ini berdampak pada perubahan struktur sosial masyarakat Bali dari feodal ke modern, dimana jaba mengalami mobilitas sosial vertikal. Hal ini pada gilirannya mengakibatkan persaingan antara bangsawan dan jaba, sehingga muncul berbagai organisasi seperti Surya Kanta dan Bali Adnyana. Organisasi Surya Kanta yang didirikan oleh para jaba melakukan gerakan sosial dengan menuntut kesetaraan dalam masyarakat, menghilangkan ajawera, menyesuaikan adat dengan perkembangan zaman, menghilangkan asupundung dan alangkahi karanghulu, dan mengembalikan sistem kasta pada prinsip-prinsip agama.